Crystallization-induced ultrafast Na-ion diffusion in nickel hexacyanoferrate for high-performance sodium-ion batteries. (January 2020) - Xu, Yue; Ou, Mingyang; Liu, Yi; Xu, Jia; Sun, Xueping; Fang, Chun; Li, Qing; Han, Jiantao; Huang, Yunhui
Abstract: Prussian blue analogues (PBAs) have attracted great interests due to their stable and open framework structures as novel electrode materials in rechargeable sodium-ion batteries (SIBs). However, Na + diffusion within electrode materials not only relates to many confined spaces formed by lattice frameworks for Na-ion storage but also highly involves with Na + migration channel generated by lattice periodic arrangement. In this work, the correlation between PBAs crystallinity and Na + insertion/extraction properties were systematically investigated. High-crystallized nickel hexacyanoferrate (NiHCF-h) exhibits a fast Na-ion migration process with a high diffusion coefficient of 8.1 × 10 −10 cm −2 s −2, and a high capacity retention of 73.7% at 4.25 A g −1 . Even crystal size is six times larger than low-crystallized nickel hexacyanoferrate (NiHCF-l), the high-crystallized NiHCF-h shows a faster Na + insertion/extraction process. The basic structural characterization and pair distribution function (PDF) analysis show that NiHCF-h has a long-range lattice periodicity, enabling Na ions transfer more easily through migration channels. This demonstrates that the crystallinity of PBAs is an extremely important factor in ionic migration process, even with proved vacancies and H2 O molecules in PBAs framework structure. Graphical abstract: Image 1 Highlights: Pair distribution function (PDF) analysis was used to to directly probe lattice periodicity of the two samples. High-crystallized structure with long-range lattice periodicity, provides smooth diffusion pathway for fast Na + migration. High-crystallized NiHCF cathode exhibit excellent rate and cyclic performances for Na + -ion batteries.